Effectiveness of Agricultural Insurance Program as A Sustainable Agricultural Development Effort - yudiarini nyoman; Luh Putu Kirana Pratiwi; Made Budiasa (Warmadewa University Press, 2022)
In an effort to develop agriculture, especially as a protection for farmers against crop failure, the provincial government of Bali through the National Food Security program has established Badung Regency as a pilot project for implementing agricultural insurance through the Jasindo Insurance Company. This concept is applied as a guarantee for farmers in terms of price fluctuations of agricultural products that tend to decline, thus triggering the reduction of agricultural terrain that increases each year in Bali Province. This study goals to analyse the level of effectiveness of the agricultural insurance program and to analyze the factors that affect the level of effectiveness of the insurance program as an attempt to develop sustainable agriculture in Bongkasa Village, Abiansemal Region, Badung Regency. The method of analysis in this research is done quantitatively, namely this study uses two analyzes, namely descriptive analysis which is used to analyze the level of effectiveness of agricultural insurance programs and Confirmatory Factor Analysis which is used to confirm latent variables and indicators. The results of the analysis show that the level of effectiveness of the agricultural insurance program is 81.75 percent with effective criteria. The variable that has a dominant affect on the performance of the insurance program as an effort to develop sustainable agriculture is the process variable which is then followed by the output variable and the input variable.